PROFILE OF LEARNING LITERACY AND NUMERACY FOR STUDENTS OF ELEMENTARY SCHOOL THROUGH CAMPUS TEACHING 3 ACTIVITIES - Amriani Amir, Asri Mulya Ashari, Warsidah, Mega Sari Juane Sofiana, Gusti Eva Tavita (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2022)
Literacy and numeracy are basic human abilities and skills in accessing and understanding everyday life phenomena, including reading, viewing, simple counting, and speaking activities. This study aimed to examine the literacy and numeracy abilities of class 3 students at Elementary School SDN No. 16 North Pontianak through Campus Teaching 3. The research was conducted using a descriptive qualitative method, where primary and secondary data were collected and then described along with factual documentation in the field. We are interviews with the principal and third-grade teachers and students of the KM3 team assigned to the class as primary data. At the beginning of the activity, several students were not fluent in reading and arithmetic. It was caused by online learning at home during the Covid 19 pandemic. The activity's end showed that all 33 students had completed reading and writing skills. They can solve thematic problems through the ability to read, count, write and listen to reading material. They were able to deal with primary operations in math, such as adding, subtracting, dividing, and multiplying numbers.